Conservation Agriculture, Crop Intensification and Cultivation of Mustard in the Northeastern Bangladesh - Islam, K. K.; Toppo, A.; Biswas, B.; Mankin, A.; Roy, S.; Paul, A.; Barman, R.; Alam, N. E. K. (International Journal of Environment, Agriculture and Biotechnology, 2022)
Deteriorating soil quality and lower crop yields due to continuous monocropping in the small-scale farmers’ fields have led to a quest for sustainable production practice with greater resource use efficiency in Bangladesh. Conservation agriculture is one such good practice that can successfully address soil quality improvements and crop productivity using locally available resources. Therefore, the objective of the study was to determine the effect of conservation agriculture practices on mustard productivity and soil quality in the northeastern region of Bangladesh. The study also cultivated mustard crops as a part of crop intensification of existing two cropping patterns into four crops. The study was conducted at two locations following Randomized Complete Block Design (RCBD) in the farmers' fields of Netrokona and Sunamganj Districts of Bangladesh during the period from November 2021 to January 2022. The results revealed that the conservation agriculture practice had significantly improved mustard seed yield and the trial variety Bangladesh Agriculture Research Institute (BARI-14) mustard produced the highest yield of 1035 kg/ha in the Dharmapasha area. In conservation agriculture practice, 50% of less fertilization, 12 t/ha organic manuring, minimum tillage, permanent crop residues and crop rotation had substantially improved the soil organic matter content, total nitrogen, phosphorous, potassium and also neutralize pH for crop cultivation. So, improvements in mustard productivity, overall economic gain and soil quality have made the conservation agriculture practice an attractive system for small-scale farmers in the northeastern region and other areas with similar conditions in Bangladesh. Thus, the present study concluded that in the next decade, agriculture will have to sustainably produce more food using less and through the more efficient use of natural resources, creating a minimum impact on soil and environment, in order to meet the demands of the growing population.